2006
DOI: 10.1021/jp057153z
|View full text |Cite
|
Sign up to set email alerts
|

Products of the Triplet Excited State Produced in the Radiolysis of Liquid Benzene

Abstract: The radiation chemical yields of the products derived from the triplet excited state produced in the radiolysis of liquid benzene with gamma-rays, 10 MeV 4He ions, and 10 MeV 12C ions have been determined. Iodine scavenging techniques have been used to examine the formation and role of radicals, especially the H atom and phenyl radical. For all irradiation types examined here, the increase in hydrogen iodide yields with increasing iodine concentration matches the increase in iodobenzene yields. This agreement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Moving from Titan's atmosphere down to Earth, biphenyl and larger polyphenyls -in addition to PAHs and carbonaceous dust particles [14,15] -have been detected in the plasma treatment of gaseous mixtures containing benzene [16,17] as well as in the radiolysis of liquid [18,19,20] and gaseous benzene [21]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Moving from Titan's atmosphere down to Earth, biphenyl and larger polyphenyls -in addition to PAHs and carbonaceous dust particles [14,15] -have been detected in the plasma treatment of gaseous mixtures containing benzene [16,17] as well as in the radiolysis of liquid [18,19,20] and gaseous benzene [21]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…1 for cyclohexane (LaVerne et al, 1992;Schuler, 1957;Enomoto et al, 2006b) Figs. 1-3 are the major products formed in radiolysis and thereby represent the main decomposition scheme. A large decrease in overall product yield is observed from cyclohexane to benzene.…”
Section: Resultsmentioning
confidence: 97%
“…Indeed, based on the scavenging experiments, Enomoto et al have concluded that triplet excited states are the precursors of phenyl radicals under radiolysis of liquid benzene. 38 If we consider the excited states resulting from ion−electron recombination, formation of triplet states (including both T 1 and higher triplets) is quite probable, and the ratio of triplet to singlet states should be 3:1 for recombination of noncorrelated pairs. The loss of spin correlation in recombining pairs is expected because both positive holes and electrons travel over large distance in solid noble-gas matrices.…”
Section: Resultsmentioning
confidence: 99%